Genetic Relationship of the Transgenic and Non-Transgenic Mutiara Catfish with their Hybrids Sangkuriang Catfish - Iskarimah Yolanisa; Ibnu Dwi Buwono; Yuniar Mulyani; Iskandar Iskandar (Jurnal Biodjati, 2019)
The male broodstock of Transgenic Mutiara catfish (P) (containing Clarias gariepinus Growth Hormone, CgGH) is a fish who show fast growth. Propagation of the Transgenic Mutiara catfish F1 and F2 progeny involves the crossing of broodstock P with Non Transgenic Mutiara catfish. New genetic variations (polymorphisms) can be generated from crosses broodstock P and F1 which lead to the fast growth inheritance of transgenic fish. Phylogenetic relationship analysis showed distance and genetic variation in broodstock P, F1, F2 and Sangkuriang catfish (as controls) using the RAPD-PCR method (Random Amplified Polymorphic DNA-Polymerase Chain Reaction) as the research purposes. The results showed that OPA-03 (5'-AGTCAGCCAC-3 ') primer was selective for determining phylogenetic among catfish samples. The closest genetic similarity index originates from the female broodstock of Non Transgenic Mutiara catfish (P) (93%), while the farthest originates from the male broodstock of Mutiara Transgenic catfish (P) (51%) with F1 dan F2. Closely related broodstock catfish is not recommended to be crossed.